2020
DOI: 10.1111/iwj.13364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acute and chronic wounds – with emphasis on pressure ulcers – in integrated continuing care units in Alentejo, Portugal

Abstract: The aim of the study was to describe the prevalence and general characteristics of acute and chronic wounds in 2018 in Alentejo (Portugal) continuing care units. In order to look at associations, wound characteristics studied were location, type, place of acquisition, number, and duration, and patient characteristics were sex, age, and presence of risk factors. During the first 2 weeks of February 2018, a total of 770 patients were assessed at continuing care units of Alentejo. Of these, 135 exhibited wounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…A point prevalence survey conducted three years later, using the same instrument in a homogenous group of patients, found that PU grades 3 and 4 continued to be the most prevalent complex wounds reported. PU represented 65.1% of all wounds [15] with poor healing rates. The literature shows that more severe stages are associated with a higher risk of complications such as critical colonisation, cellulitis, osteomyelitis, increased costs [16,17] and potential death.…”
Section: Of 12mentioning
confidence: 99%
“…A point prevalence survey conducted three years later, using the same instrument in a homogenous group of patients, found that PU grades 3 and 4 continued to be the most prevalent complex wounds reported. PU represented 65.1% of all wounds [15] with poor healing rates. The literature shows that more severe stages are associated with a higher risk of complications such as critical colonisation, cellulitis, osteomyelitis, increased costs [16,17] and potential death.…”
Section: Of 12mentioning
confidence: 99%
“…52,53 Chronic wounds are often caused by chronic diseases and complications caused by their care, and even acute wounds caused by improper treatment or infection (such as diabetic foot ulcers, acute orthopedic wounds, venous leg ulcers, ischemic ulcers, pressure ulcers, etc.). [54][55][56][57] In chronic wounds, common features are usually depicted compared with normal wound healing, including nonmigrating epidermis, unresolved inflammation, fibrosis, presence of infection, and biofilm formation (Figure 1). Although there is an increase in neutrophils and macrophages, not all are properly functioning.…”
Section: Bacteria-infected Wound Healing and Treatmentmentioning
confidence: 99%
“…Literatürde periferik dolaşım bozukluğu, kardiyovasküler sorunlar, diyabetes mellitus, nörolojik hastalıklar, beslenme sorunları vb. gibi yara oluşumu ve iyileşmesi üzerinde etkili pek çok risk faktöründen bahsedilmektedir (13,14). Çalışmadan elde edilen bulgulara bakıldığında hastaların çoğunluğunun diyabet (%75,9), kalp (%50) ve dolaşım sistemi (%43,7) hastalığı tanısı olduğu belirlenmiştir.…”
Section: Gereç Ve Yöntemlerunclassified